The four types of knowing : metaphysical, scientific, narrative, and pragmatic : a meta-epistemology of mind - Pietersen, H. J. (Herman Johan), 1950- (Edwin Mellen Press, 2011)
This book provides a fundamental and integrated framework of human thought, beyond the confines of any particular knowledge discipline or tradition. It serves to highlight the intellectual strengths and limitations of each modality and is therefore useful for comparative purposes.